2015
DOI: 10.1371/journal.pone.0122233
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Pathogen-Responsive Proteins from Apple Leaves Induced by the Alternaria Blotch Alternaria alternata

Abstract: Understanding the defence mechanisms used by apple leaves against Alternaria alternate pathogen infection is important for breeding purposes. To investigate the ultrastructural differences between leaf tissues of susceptible and resistant seedlings, in vitro inoculation assays and transmission electron microscopy (TEM) analysis were conducted with two different inoculation assays. The results indicated that the resistant leaves may have certain antifungal activity against A. alternate that is lacking in suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…HSP20s , for example, did not respond at early stages of infection but slightly increased at later stages. In contrast, many of HSP70 transcripts were down-regulated (Figure 8B), a result confirmed by a proteomics study of apple-AAAP interactions that showed that these proteins accumulate in resistance as opposed to susceptible leaves (Zhang et al, 2015). Additional research has shown that HSP70s are induced by both P. expansum and P. digitatum pathogens in “Ultima Gala” apple cultivar (Spadoni et al, 2015), thus expression of these proteins is an important fact of apple disease-resistance.…”
Section: Resultssupporting
confidence: 67%
“…HSP20s , for example, did not respond at early stages of infection but slightly increased at later stages. In contrast, many of HSP70 transcripts were down-regulated (Figure 8B), a result confirmed by a proteomics study of apple-AAAP interactions that showed that these proteins accumulate in resistance as opposed to susceptible leaves (Zhang et al, 2015). Additional research has shown that HSP70s are induced by both P. expansum and P. digitatum pathogens in “Ultima Gala” apple cultivar (Spadoni et al, 2015), thus expression of these proteins is an important fact of apple disease-resistance.…”
Section: Resultssupporting
confidence: 67%
“…On the basis of AM-toxin acting site and known pathogenesis, it is identified that Alternaria alternata f. sp. mali pathogen may secrete AM-toxins that act on the susceptible leaf cells causing tissues damage (Zhang et al, 2015 ).…”
Section: Important Hsts Produced By Alternaria Spementioning
confidence: 99%
“…Alternaria alternata leaf spot is a major fungal disease of apple (Malus × domestica). (Zhang et al, 2015). In general, when fungi attack apple leaves, they produce toxins and effectors, which disrupt plant metabolism (Hugot et al, 1999;Johnson et al, 2000;Abe et al, 2010), leading to H 2 O 2 accumulation and cell death (Chung, 2012).…”
Section: Introductionmentioning
confidence: 99%